DATA ACQUISITION OF POSITION AND SPEED OF ROTOR WITH ROTARY ENCODER AND MEASUREMENT OF CONTROL PARAMETERS ON SWASHPLATELESS COAXIAL DRONE SYSTEM - Rasyid Fadlurrahman, Nur
UAV(Unmanned Aerial Vehicle) or can be called drone have very rapid development at this time. Along with these developments, we found that drone can be controlled well with just two propellers. To move in the horizontal plane, the drone needs to change its orientation by doing pitch and roll. In this final project, the implementation of a swashplateless system will be discussed that can overcome this problem. Mechanically, this system can change the orientation of the propeller angle aerodynamically. This system is implemented by utilizing a microcontroller that converts PWM signals from commercial Flight Controllers into cyclic control signals.This control have advantages where the drone can be stabilized when flying in the sky, with the result that the camera can be implemented with no stabilizer like gimbal. The implemented cyclic control is a control of changes in rotor speed in one rotation. By controlling the speed at a certain angle, there will be an increase of force on one side of the propeller and the orientation of the propeller angle will change. In developing this system, a rotary encoder is needed to detect the position and speed of the rotor in the system. In this flight system also need to know also the parameters that affect the condition of flying drones when controlled. This control parameter is obtained from mathematical calculations based on the aerodynamic theory applied to the UAV.